Pembaharuan Atas Hukum Keluarga di Indonesia: Satu Tinjauan Sosiologis - Munawir Haris (Ulumuna, 2015)
The renewal of Islamic law is essentially contrary to something that already exists (existing) then undergoes a qualitative change as a product of interaction in public life. It could be argued that the process of renewal of Islamic law is seen as something autonomous, but it also interacts with other elements in society that occur interdependently. Therefore, the concept of renewal of Islamic law requires adaptive stance with social conditions in which it interacts. In this case, the realization of the principle of al-muh}āfaz}atu ‘alā al-qadīmi al-s\ālih} wa al-akhdhu bi al-jadīd al-as\lah} (Maintaining the old one if it is still good and accept the new or changed if it is considered better) became a necessity. Within the framework of family law renewal in Indonesia, Islamic law has a very strategic and important role. From the sociological point of view, Islamic family law has deeply rooted in the Muslim daily live and become a living law in the midst of the majority of Indonesian people. Renewal of Islamic law in the context of family law in Indonesia includes four categories namely fiqh, fatwā, jurisprudence and legislation. This article explores these four categories and shows how reform influence these domains. DOI: http://dx.doi.org/10.20414/ujis.v19i1.1254